Spatial-Material Memory Pedagogy: Deconstructing the Educational Model of Deuteronomy 6:4-9 in Digital Learning Spaces - Sukanto Limbong; Daniel Razsekar Panjaitan (Global Education Journal, 2026)
The rapid migration of contemporary education into virtual environments has engineered an ontological crisis characterized by disembodied learning and digital learning space alienation. As instructional interactions are reduced to frictionless screens, students are increasingly severed from the physical geographies and tangible materials vital for shaping ethical consciousness and collective memory. This study addresses this theoretical gap by executing a qualitative deconstruction of Deuteronomy 6:4–9, reframing it from a narrow theological dogma into an ancient Near Eastern curricular artifact of resilience. Grounded in philosophical-pedagogical hermeneutics and a Derridean deconstructive approach, the study analyzes the semantic and syntactic functions of the Hebrew Masoretic text's spatial-itinerant verbs (yashab, halak, shakab, qum) and material-semiotic objects (’oth, totaphoth, mezuzah), dialectically juxtaposing them with contemporary frameworks of spatial pedagogy and new materialism. The analysis extracts a novel conceptual model termed the "Spatial-Material Pedagogy of Memory." The findings reveal that verse 7 establishes a "Liquid yet Place-Anchored Curriculum" that reclaims everyday geographical trajectories against digital non-places, while verses 8–9 deploy a "Curriculum of Materiality" that utilizes physical tokens and architectural thresholds to counteract digital amnesia through embodied cognition. Ultimately, this model destabilizes the technocentric hegemony of modern educational technology, offering a robust philosophical foundation for future hybrid curricula that intentionally bind digital tools to local physical ecologies and corporeal craftsmanship.